Strategi Komunikasi Pemasaran Dalam Membangun Awareness Produk Ramah Lingkungan Pada Pt.Virtus Venturama: ( Studi Kasus Pada PT.Virtus Venturama) - Cindya Yunita Pratiwi Cindya Yunita (Jurnal Spektrum Komunikasi, 2020)
Environmental problems are a major factor not only for now but also for the future. The problem of non-recyclable waste is usually due to plastic packaging that accumulates and doesn’t decompose in a short period of time, therefore the author chooses research at PT Virtus Venturama as an environmentally friendly packaging product, a type of qualitative research with study methods case. PT.Virtus Venturama strives to contribute to environmental sustainability by producing product packaging that is environmentally friendly, and safe for health, this research will discuss how the Marketing Communication Strategy implemented by PT. Virtual in building awareness of Eco-friendly products not only for the community but especially business people or businesses in the culinary field